Mentorship: A process of nurturing others - Masango, Maake (HTS teologiese studies, 2011)
This article is dedicated to Prof. Dr Andries van Aarde who has mentored a large number of students during his time as a lecturer at the University of Pretoria. It is written at the time when workers in South Africa are striking. Industrial psychologists are involved in mediation and aim to develop a culture of understanding between workers and management. The article analyses some causes of tension between managers and workers in the South African context and indicates how mentorship may help to foster growth amongst workers and managers. A case study explores the issue of cultural differences which often lead to misunderstandings, especially when managers do not understand the world in which workers live. The aim of the article is to contribute to existing insights that may help to create a healthy working relationship between managers and workers which will benefit both.